1993
DOI: 10.1055/s-2007-994770
|View full text |Cite
|
Sign up to set email alerts
|

Ionized Serum Magnesium Levels in Umbilical Cord Blood of Normal Pregnant Women at Delivery: Relationship to Calcium, Demographics, and Birthweight

Abstract: Using a novel ion-selective electrode for ionized Mg (IMg2+), we sought to: (1) determine levels and fractions of IMg2+ in umbilical vessels of normal pregnant women: (2) determine their relationships with ionized calcium (ICa2+) levels: (3) determine whether any demographic or clinical parameters affect these levels of divalent cations: and (4) compare levels of IMg2+, total Mg, percent IMg2+, and ICa2+ with sera of normal pregnant and nonpregnant women. We obtained umbilical arterial and venous serum from 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…Our present results confirm and extend previous studies [3,5] and point most strongly to the facts that the hemodynamically and otherwise important biologically active divalent cation magnesium and the ionized Ca/Mg ratio circulating in the blood are somehow intimately related to the sex hormone levels in women, whether they are normal adults of child-bearing age [3], post-menopausal [5], pregnant [7][8][9][10][11] or pharmacologically altered (present study).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our present results confirm and extend previous studies [3,5] and point most strongly to the facts that the hemodynamically and otherwise important biologically active divalent cation magnesium and the ionized Ca/Mg ratio circulating in the blood are somehow intimately related to the sex hormone levels in women, whether they are normal adults of child-bearing age [3], post-menopausal [5], pregnant [7][8][9][10][11] or pharmacologically altered (present study).…”
Section: Discussionsupporting
confidence: 92%
“…The Ca 2+ /Mg 2+ ratios were calculated (using the measured Ca 2+ and Mg 2+ values), as was the percent ionized Mg 2+ . The normal reference ranges for our laboratory are as follows: Ca 2+ 1.09-1.33 mmol/l; Mg 2+ 0.54-0.64 mmol/l; total Mg 0.74-0.96 mmol/l [7].…”
Section: Hormone and Cation Assaysmentioning
confidence: 99%
“…In two studies performed on pediatric intensive care patients (32) and 22 newborns with hypomagnesemia (33), it was shown that serum total Mg levels may not correlate with IMg levels and that IMg measurement best provides a more relevant assessment of Mg homeostasis. In one of the initial studies conducted by using ISE method in umbilical cord blood samples, Handwerker et al (24) reported umbilical venous IMg levels (0.49 -0.53 mM) a little higher than umbilical arterial ones (0.46 -0.5 mM). In another study aiming to determine normative data in healthy term newborns (22), IMg levels were investigated in umbilical venous blood of 30 newborns at birth and in peripheral venous blood of 32 newborns at 24 h of life, and normal ranges of IMg in both groups reportedly were between 0.4 and 0.56 mM.…”
Section: Discussionmentioning
confidence: 99%
“…Although these levels are similar and close to those in the previously published studies on newborns, the relatively wider ranges in our study may have resulted from the mean postnatal age (156.1 Ϯ 46.5 h) of the cases, considering physiologic changes in Mg levels during the first week of life. Previously published neonatal IMg studies (22)(23)(24) have been conducted in exclusively healthy newborns during the first 24 -72 h of life. The high serum bilirubin levels also may have contributed to greater variability of IMg; high IMg levels (0.6 Ϯ 0.12 mM) in the group of severe hyperbilirubinemia in our study further supports this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation